The Retreat - Context and Response: Manhattan, Kansas/Manhattan, New York - Shannon Criss (Oz, 1985)
The notion of "getting away from it all" has existed in the human race for generations, from Emperor Hadrian to King Henry the XIV, to Jefferson and Ronald Reagan. But not all are able to have their own villa to escape to, away from the daily confusion...